4th AIAA Atmospheric and Space Environments Conference 2012
DOI: 10.2514/6.2012-3035
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Mixed-Phase Icing with Application to Ice Crystal Accretion in Aircraft Jet Engines

Abstract: This paper describes experiments performed in an altitude chamber at the NationalResearch Council of Canada (NRC) as the first phase of a joint NRC/NASA program investigating ice crystal accretion in aero engines. The principal objective was to explore the effect of wet bulb temperature T wb (dependent on air temperature, humidity and pressure) on accretion behavior, since preliminary results published in an earlier paper indicated that well-adhered accretions are only possible at T wb <0°C, when water in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 6 publications
3
78
0
Order By: Relevance
“…This is confirmed by experiments that have been conducted by Currie et al [23]. In these experiments the effect of the wet bulb temperature on the accretion behaviour has been studied in the altitude test facility of NRC (RATFac).…”
Section: Rime Ice Regimesupporting
confidence: 69%
See 4 more Smart Citations
“…This is confirmed by experiments that have been conducted by Currie et al [23]. In these experiments the effect of the wet bulb temperature on the accretion behaviour has been studied in the altitude test facility of NRC (RATFac).…”
Section: Rime Ice Regimesupporting
confidence: 69%
“…• C. From these experiments, and those on the double-wedge aerofoil (Currie et al [23]), it has been concluded that erosion of ice accretions mainly depends on the tangential velocity of the impinging ice crystals and that it scales with that velocity to a power 2 or 3. This conclusion has been based on the observation that adding ice crystals to a free stream with a wet bulb temperature below freezing led to an increase of ice growth on the leading edge, but to a decrease of ice growth further downstream.…”
Section: Erosionmentioning
confidence: 99%
See 3 more Smart Citations